2021
DOI: 10.1245/s10434-021-09627-2
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Socioeconomic Status on Presentation and Outcomes in Colorectal Peritoneal Metastases Following Cytoreduction and Chemoperfusion: Persistent Inequalities in Outcomes at a High-Volume Center

Abstract: Background Cytoreductive surgery and hyperthermic intraperitoneal chemoperfusion (CRS HIPEC) can offer significant survival advantage for select patients with colorectal peritoneal metastases (CRPM). Low socioeconomic status (SES) is implicated in disparities in access to care. We analyze the impact of SES on postoperative outcomes and survival at a high-volume tertiary CRS HIPEC center. Patients and Methods We conducted a retrospective cohort study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
(20 reference statements)
1
14
1
Order By: Relevance
“…We also found that the occurrence of a major complication postoperatively was associated with overall survival. This agrees with results from a similar study investigating colorectal cancer patients undergoing CRS and HIPEC ( 7 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that the occurrence of a major complication postoperatively was associated with overall survival. This agrees with results from a similar study investigating colorectal cancer patients undergoing CRS and HIPEC ( 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…This finding contrasts the results reported by Rieser et al. who found that for colorectal cancer patients with peritoneal carcinomatosis, patients with lower socioeconomic status had longer lengths of stay, more complications, and higher rates of 90-day readmission and 30-day mortality ( 7 ). The authors argued that patients with lower socioeconomic status experience multiple disadvantages and worse overall survival compared to higher socioeconomic status patients that was not explained by individual cancer biology characteristics.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…There is relatively little published about social disparities and CRS/HIPEC, although one of the largest to date is by Rieser et al 17 who studied the impact of SES on 226 patients who underwent CRS/HIPEC for colorectal peritoneal metastases. They found that high‐SES patients were more likely to be white, privately insured, and had fewer comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] While multiple studies have examined the impact of social determinants of health on gastrointestinal malignancies, few studies have examined the effect specifically on patients with peritoneal malignancies undergoing cytoreductive surgery (CRS) and heated intraperitoneal chemotherapy (HIPEC). 17 This patient population is uniquely vulnerable due to the high morbidity and mortality of the required operations, in addition to the complex pre-and postoperative care that is often needed to successfully care for these patients. They often have severe protein malnutrition perioperatively, and can have complex home-care needs including ostomies, drains, nutritional supplements, and wound care.…”
mentioning
confidence: 99%